2014
DOI: 10.1186/preaccept-6783991421275553
|View full text |Cite
|
Sign up to set email alerts
|

Loss of LKB1 disrupts breast epithelial cell polarity and promotes breast cancer metastasis and invasion

Abstract: Background: LKB1, also known as STK11, is a master kinase that serves as an energy metabolic sensor and is involved in cell polarity regulation. Recent studies have indicated that LKB1 is related to breast tumorigenesis and breast cancer progression. However, little work has been done on the roles of LKB1 in cell polarity and epithelial-mesenchymal transition in breast cancer. In this study, we tried to prove that loss of LKB1 disrupts breast epithelial cell polarity and causes tumor metastasis and invasion. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…The parent of the LCC6 cells, the MDA-MB-435 cell line, is highly metastatic and expresses many of the classic EMT markers such as low levels of E-cadherin and high levels of Vimentin, N-cadherin, and alpha smooth muscle actin (Li, et al 2014; Manni, et al 2002). In the current study, we show down-regulated expression of mesenchymal markers including Vimentin, TWIST1, SLUG (SNAIL family transcription factor) and ZEB1 at RNA and protein levels in the tumors with IR knockdown.…”
Section: Discussionmentioning
confidence: 99%
“…The parent of the LCC6 cells, the MDA-MB-435 cell line, is highly metastatic and expresses many of the classic EMT markers such as low levels of E-cadherin and high levels of Vimentin, N-cadherin, and alpha smooth muscle actin (Li, et al 2014; Manni, et al 2002). In the current study, we show down-regulated expression of mesenchymal markers including Vimentin, TWIST1, SLUG (SNAIL family transcription factor) and ZEB1 at RNA and protein levels in the tumors with IR knockdown.…”
Section: Discussionmentioning
confidence: 99%
“…MCF10A cells were cultured as previously described. 57 MCF12A cells were cultured in the same way as the MCF10A cells. The cells were incubated in 5% CO 2 at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, under the stress, energy demand or energy supply imbalance conditions that are typical requirement of the tumor microenvironment leads to increase in the expression of AMPK that alters the cancer cell's flexibility to utilize nutrient glucose directly (Liang and Mills 2013;Herrmann et al 2011). Other studies reported that the knockdown of STK11 in MCF-7 and MDA-MB-435 cells induced migration and invasion of breast cancer cells due to which loss of cell polarity and cell-cell adhesion occurs (Li et al 2014;Zhuang et al 2006).…”
Section: Discussionmentioning
confidence: 99%